1986
DOI: 10.1007/bf01324823
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of auditory responsiveness in the locust

Abstract: The auditory responsiveness of a number of neurones in the meso- and metathoracic ganglia of the locust, Locusta migratoria, was found to change systematically during concomitant wind stimulation. Changes in responsiveness were of three kinds: a suppression of the response to low frequency sound (5 kHz), but an unchanged or increased response to high frequency (12 kHz) sound; an increased response to all sound; a decrease in the excitatory, and an increase in the inhibitory, components of a response to sound. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 39 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…This neuron's structure is obviously homologous to the AN4-neuron described in Locusta migratoria (compare Fig. 2a and b; see also R6mer and Marquart 1984; synonymous: neuron 541, Boyan 1986). We will use the term AN4 for Ch.…”
Section: Interneuron Morphologysupporting
confidence: 54%
“…This neuron's structure is obviously homologous to the AN4-neuron described in Locusta migratoria (compare Fig. 2a and b; see also R6mer and Marquart 1984; synonymous: neuron 541, Boyan 1986). We will use the term AN4 for Ch.…”
Section: Interneuron Morphologysupporting
confidence: 54%
“…Appropriate voltages of stimulation produced a single volley arriving at the terminals of afferents or interneurons, as previously described (Pearson et al, 1985;Boyan, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…Wind stimulation of filiform afferent hairs on the cerci can elicit jumping (Hoyle, 1958) and flight (Boyan et al, 1986) in the locust, kicking in the cricket (Huber, 1965), escape running in the cockroach (Camhi, 1980); the cerci are vital for flight stabilization in both the cockroach (Fraser, 1977) and locust (Altman, 1983). Cereal position, in particular, has been shown to determine the directionality of GINS in some species (Rozhkova, 1980;Rozhkova et al, 1984), and in the cockroach, behavioral compensation has been demonstrated in response to experimentally altered cereal position (Comer and Camhi, 1984).…”
Section: Functional Attributes Of the Pad Unitmentioning
confidence: 99%
See 1 more Smart Citation